The Great Himalaya Trail: A New Nepal Tourism Product with Both Trek Marketing and Development Rationale - Choegyal, Lisa (Nepal Tourism and Development Review, 2013)
DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7371 Nepal Tourism and Development Review Vol.1(1) 2011 71-76